Synthesis of Zinc Oxide Nanoparticle Using Mushroom Extract to Carry Drug Compounds - Malinie Rajasingam (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To synthesize zinc oxide nanoparticles using mushroom extract under optimal conditions. To examine the morphological and structural characterizations of synthesized zinc oxide nanoparticle. To prepare drug carry compound using synthesize zinc oxide nanoparticle and evaluate the antimicrobial potential.